Knowledge of sports participants about dental emergency procedures and the use of mouthguards - (:unkn) unknown (WILEY, 2014)
AimThe aim of this study was to evaluate the knowledge of sports participants regarding emergency management of dental trauma and the awareness about mouthguards. MethodsA specific questionnaire regarding knowledge, experiences and behaviours after dental trauma and the use of mouthguard was distributed to 359 sports participants up to 18years of age. The sports involved were basketball, swimming, volleyball, soccer, tennis, badminton, handball, athleticism, golf, gymnastics, water polo and karate. The questions were focused on personal experience, awareness of first aid and dental emergency procedures and knowledge about mouthguards. ResultsThe results showed that 10.9% had experienced a kind of dental trauma, and 12.5% would look for a dentist for treatment in emergency. 34.5% would re-implant the avulsed tooth, 33.4% would maintain the avulsed tooth in handkerchief and 25.3% would maintain it in saline solution. 41.1% were aware of the possibility of oral injuries during sports practice, and 55.4% knew about mouthguards, but only 11.2% of the participants reported to use them. There was a statistically significant difference between the experienced participants (>5years) and less-experienced group (<5years) in knowledge about dental emergency procedures and mouthguards. Reasons given for not wearing mouthguards include lack of aesthetic' was significantly high in experienced participants. The less-experienced participants significantly stated that they had never heard about mouthguards before. ConclusionOur results showed a lack of knowledge of sports participants about management and prevention of traumatic dental injuries. Educational programs should be organized to give information about emergency treatment and promote the use of mouthguards to sport participants.
Keywords: contact sports; dental trauma; mouthguard; OROFACIAL INJURIES; TRAUMA; INFORMATION; PLAYERS; LEVEL